Expanding cities - diminishing space: will cities remain liveable, accessible, human-oriented places: for whom and how? - Ryser, Judith (My University, 2018)
The CORP 2018 brief of "Expanding Cities - Diminishing Space" rests on the unassailable credo in techno-fixes. The argument here is that while technologies have always influenced urban change, cities have evolved with techno-fixes in combination with many other development processes. As evidence shows that with globalisation development has become more unevenly distributed in urban space what matters is whether techno-fixes are contributing or alleviating uneven spatial and social justice and urban quality of life.
Keywords: Stadtentwicklung; Stadtwachstum; Transformation; Smart City; Neue Technologie; Technischer Fortschritt; Planungstheorie